Towards practical intrusion detection system over encrypted traffic. (21st March 2021) - Canard, Sébastien; Li, Chaoyun
Abstract: Privacy and data confidentiality are today at the heart of many discussions. But such data protection should not be done at the detriment of other security aspects. In the context of network traffic, intrusion detection system becomes totally blind when the traffic is encrypted, making clients again vulnerable to known attacks. To reconcile security and privacy, BlindBox and BlindIDS are proposed to perform Deep Packet Inspection over an encrypted traffic, based on two different cryptographic techniques. But, on one side, even if BlindBox is quite efficient to detect an anomalous encrypted traffic, it necessitates a very high setup time for clients and servers and does not protect the know‐how of Security Editors (SEs) working on detection rules. On the other side, BlindIDS does protect SE's market and does not introduce any latency during setup time, but is definitely not enough efficient for a practical use. Herein, it is shown that the design of a fully efficient and market‐compliant intrusion detection system over an encrypted traffic is possible. The system is based on only symmetric cryptography, and permits to encrypt a packet of 1500 bytes in about 6 μs and to test such packets with 3000 rules in less than 2 μs.